Synthesis, Characterization, and Biological Activities of Novel Schiff Bases Derived from 3-acetyl-4-hydroxy-2h-chromen-2-one and 5-(4-ethoxy/ halo substituted phenyl)-1,3,4-oxadiazol-2-amine - Jadhav R. L.; Ubale S.B. (International Journal of Scientific Research in Science and Technology, 2024)
Five novel Schiff base ligands (5a-e) were synthesized by condensing 3-acetyl-4-hydroxy-2H-chromen-2-one with 5-(4-ethoxy/ halo substituted phenyl)-1, 3, 4-oxadiazol-2-amine. Their structures were confirmed using different methods like elemental analysis, infrared spectra, 1H and 13C NMR, and mass spectroscopy. The antibacterial and antifungal activity of the synthesized compounds was studied against selected bacterial cultures; gram- negative E. coli, S. typhi and gram-positive S. aureus, B. subtilis. It was observed that all the compounds except 5a showed strong antibacterial effects against these bacteria, similar to penicillin, which is a standard antibacterial drug, because they contain halogen elements. Furthermore, they underwent testing against fungi like A. niger, P. chrysogenum, F. moniliforme and A. flavus, employing the poison plate method. Compound 5a had moderate antifungal activity compared to 5b-e. Compounds 5b-e showed excellent antifungal activity, similar to Griseofulvin, a standard antifungal drug. In brief, it may be concluded that antimicrobial activity may be attributed to the presence of both the Coumarin and oxadiazole moiety in the molecule.
Keywords: Coumarin; -acetyl-4-hydroychromen-2-one; 5-(4-ethoxy/ halo substituted phenyl)-1; 4-oxadiazol-2-amine; Schiff bases